Exploring the Intricacies of Carotid Cavernous Fistula: A Case Series: Poster Presentation - Case Series - Resident - SAPHIRA EVANI; PUTU YULIAWATI; NI MADE LAKSMI UTARI (Majalah Oftalmologi Indonesia, 2023)
Introduction : Carotid cavernous fistula (CCF) is caused by an abnormal connection between the carotid artery and the cavernous sinus, which can lead to eye-related problems. It is crucial to recognize its signs, as they can resemble other conditions. Case Illustration : First patient is a male 3-month-old baby, with unilateral right eye proptosis that was observed soon after birth and history of hypothyroid. Proptosis is more prominent while the baby is crying. Orbital ultrasonography revealed ophthalmica vein dilatation with S configuration, complex flow, and velocity of 10 cm/s. Second case is a 50-year-old male also with unilateral proptosis and orbital bruit with history of head trauma 2 months prior to admission. Patient came with complain of sudden blurry vision for 1 week. The results of the magnetic resonance venogram revealed tortuos dilated superior ophthalmica (SOV), cavernous sinus bulging, and dilated superior petrosal, sigmoid, transverse sinus, and internal jugular vein. Discussion : CCFs can occur at any age, but are more common between 40-60. Risk factors like head trauma, hypertension, connective tissue disorders increase the likelihood of developing CCF. They are often misdiagnosed as other conditions such as thyroid ophthalmopathy or conjunctivitis. Ocular doppler ultrasound can detect SOV dilation and arterial flow, while magnetic resonance imaging can show superior ophthalmic vein engorgement, muscle hypertrophy, and cavernous sinus dilatation. Treatment for symptomatic CCFs involves endovascular obliteration using balloons, embolic agents, or metallic coils, while asymptomatic and mildly symptomatic patients can be treated conservatively. Conclusion : Awareness of CCF symptoms, varied workup, prompt treatment is important to prevent severe complications.